The Lord of Glory : Meditations on the person, the work and glory of our Lord Jesus Christ - Gaebelein, Arno Clemens, 1861-1945 (Salt Lake City, UT : Project Gutenberg, 2009)
"The Lord of Glory" by A. C. Gaebelein is a collection of meditations on the life, work, and triumph of Jesus Christ, written in the early 20th century. The book explores the profound significance of Christ's person and glory, addressing the Christian believer's relationship with Him. It focuses on themes such as His preeminence, the importance of recognizing His glory in a world that often denies it, and the encouragement to reflect on His redemptive works. The opening of the book begins with an introductory preface in which the author expresses the necessity of understanding and proclaiming the glory of Christ, especially in times of increasing skepticism and denial of His divine nature. Gaebelein emphasizes that these meditations aim to inspire believers to deepen their knowledge and appreciation of Christ, as He is worthy of all honor and glory. Through references to scripture and theological reflections, the beginning sets the tone for a reverent exploration of Jesus as the Lord of Glory, establishing a foundation for understanding His significance in Christian faith and practice. (This is an automatically generated summary.)
Release date is 2009-07-31
Produced by Keith G. Richardson
Keywords: Jesus Christ -- Person and offices; Jesus Christ -- Meditations